Screw-Type Symmetry in Machine Components and Design at Implementation on a 3D Printer - Sheyko, T.I.; Maksymenko-Sheiko, K.V.; Morozova, A.I. (Проблеми машинобудування, 2019)
In this paper, the R-functions theory is used for the mathematical and computer modeling of geometric objects with a screw-type symmetry for the case when 3D printing technology is to be implemented. У цій роботі застосовується теорія R-функцій для математичного та комп'ютерного моделювання геометричних об'єктів з гвинтовим типом симетрії під час реалізації технології 3D-друку. В данной работе применяется теория R-функций для математического и компьютерного моделирования геометрических объектов с винтовым типом симметрии при реализации технологии 3D-печати.